Ocean engineering mechanics with applications - McCormick, Michael E. 1936- (Cambridge University Press, 2010)
Ocean Engineering Mechanics provides an introduction to water waves and wave-structure interactions for fixed and floating bodies. Linear and nonlinear regular waves are thoroughly discussed, and the methods of determining the averaged properties of random waves are presented. With this foundation in wave mechanics, applications to engineering situations in the coastal zone are then presented. This introduction to the coastal engineering aspects of wave mechanics includes an introduction to shore protection. Covered within are also the basics of wave-structure interactions for situations involving ridged structures, compliant structures, and floating bodies in regular and random seas. The final chapters deal with the various analytical methods available for the engineering analyses of wave-induced forces and motions of floating and compliant structures in regular and random seas. An introduction to the soil-structure interactions is also included. The book can be used for both introductory and advanced courses in ocean engineering mechanics